Numerical Simulation of Radiolysis Gas Detonations in a BWR Exhaust Pipe and Mechanical Response of the Piping to the Detonation Pressure Loads - Kuznetsov, Mike; Lelyakin, Alexander; Breitung, Wolfgang (IntechOpen, 2010)
None